Sustainable Development Goals: Parking Attendants' Decent Work Challenges and Policies - CHRISTMAS, Sandy Kurnia; ANGELIQUE, Aurellia; ANNISYAPUTRI , Annisyaputri; VITRANILLA, Yudith Evametha (Community Services: Sustainability Development, 2023)
Sustainable Development Goals are an agenda to increase inclusive economic growth in a region. As the capital of West Kalimantan Province, Pontianak City has a vital role in increasing the realization of this development by implementing policies oriented towards sustainable development, specifically in fulfilling access to decent work in Pontianak City. One of the employment sectors that is of concern is providing parking attendants with decent work access. This research examines whether the fulfillment of access to decent work for parking attendants has been fully fulfilled by looking at access to the fulfillment of human rights and compliance with the laws regulated in existing regulatory policies in the City of Pontianak. This research was carried out using socio-legal research methods, as it will examine social rules that are confirmed based on existing laws in legislation. This research shows that several indicators still need to be met to fulfill access to decent work within the standards set in the Sustainable Development Goals. One aspect of access to decent work for parking attendants that needs to be met is that social security still needs to be a priority, as well as the lack of availability of laws governing parking management in Pontianak City. So, there needs to be consideration and strengthening in fulfilling the law so that parking attendants get clear legal status and legal availability to realize decent work and economic growth according to the 8 Sustainable Development Goals.